Role of Breast Imaging Radiologists as Advocates for Screening Mammography. Issue 3 (10th April 2020) - Omofoye, Toma S; Parikh, Jay R
Abstract: The objective of this article is to outline opportunities for breast imaging radiologists to advocate for screening mammography. Despite breast cancer being the second most common cancer in women and screening mammography's ability to reduce mortality from this disease, there remains suboptimal utilization in the community. The different guidelines for screening presented by respected organizations has created confusion for patients and referring clinicians and the eventual underutilization of screening mammography. As experts in the value of early detection, breast radiologists are well suited to take on the role of screening advocates. Using specific action steps and examples, we create a template for a radiologist to utilize in the promotion of screening among the breast imaging team, clinicians, administrators, and the community at large. By deliberately filling the role of screening mammography advocate, one can satisfy the mandate for radiologists to bring increased value to the health care team while contributing to community health and patient satisfaction.